THE DILEMMA OF DEMAND SIDE POLICIES VERSUS SUPPLY SIDE POLICIES FOR RELAUNCHING CAPITALIST ECONOMIES - PETRE PRISECARU (Global Economic Observer)
The first important economic recession in this century started in USA with the burst of real estate bubble followed by the bankruptcy of some investment and commercial banks and the collapse of capital market. The financial-banking crisis spilt over the world economy and caused the second deepest economic recession in the last 80 years. The financial crisis has badly affected almost all market economies and was the result of a combination between market failures and mistakes made in macroeconomic policies. In the financial sector there was not enough regulation and supervision of corporate governance while in goods industry the pressure of over-regulation led to higher factor costs and supply contraction. The direct result of supply side policies and particularly of monetarist instruments is seen now clearly in the USA: large deficits, huge debts, reduced savings, heavy dependence on foreign money (capital) and resources, relatively low domestic output and supply.